Variation, Heritability, Genetic Gain and Correlation in White Mulberry (Morus alba Linn.) Clones - Thakur, I.K. (Indian Forester, 2018)
Variability among different traits alongwith their inter - relationship were studied in twenty seven clones of Morus alba . Significant differences were observed among clones with respect to various morphometric traits. Moderate phenotypic coefficient of variation (PCV), genotypic coefficient of variation (GCV), heritability and genetic gain were recorded for green leaf yield, plant height, leaf length, leaf width and basal diameter indicating that these characters can be more reliable for effective selection in future. Plant height showed positive and significant correlation with basal diameter, number of branches, leaf length and green leaf yield. Basal diameter, leaf length and leaf width also exhibited positive and significant correlation with green leaf yield. Therefore, these correlations can be useful in the indirect selection of white mulberry. However, rest of the correlations were non-significant.